2019
DOI: 10.1063/1.5082254
|View full text |Cite
|
Sign up to set email alerts
|

Interface resonance in Fe/Pt/MgO multilayer structure with large voltage controlled magnetic anisotropy change

Abstract: Electric control of magnetism has been a topic of interest for various spintronic applications. It is known that monoatomic Pt layer insertion at the Fe/MgO interface increases voltage-controlled magnetic anisotropy (VCMA). However, the reason for the optimality of this thickness has not been explained thus far. In this study, we observed the changes in the electronic states at the Fe/MgO interface using tunneling spectroscopy on an epitaxial Fe(001)/Pt/MgO(001) structure to characterize the density of states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We employed the molecular beam epitaxy (MBE) method to fabricate the V/Fe/MgO trilayer on an MgO (001) single-crystalline substrate (Figure a). , Prior to the deposition, we annealed the substrate at 800 °C for 10 min. A 5 nm thick MgO seed layer was first grown at a rate of 0.1 Å/s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed the molecular beam epitaxy (MBE) method to fabricate the V/Fe/MgO trilayer on an MgO (001) single-crystalline substrate (Figure a). , Prior to the deposition, we annealed the substrate at 800 °C for 10 min. A 5 nm thick MgO seed layer was first grown at a rate of 0.1 Å/s.…”
Section: Methodsmentioning
confidence: 99%
“…An Fe layer (0.7 nm, 5 ML) and MgO overlayer (2 nm) were deposited at rates of 0.05 and 0.1 Å/s, respectively. A V buffer layer was employed to induce PMA at the Fe/MgO interface , and to achieve atomically flat interfaces with minimal lattice defects . All the depositions were conducted at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies also reported an improved VCMA effect in Fe/Pt/MgO or CoFe/Ir/MgO structures by inserting an ultrathin HM layer of Pt or Ir at the FM/oxide interface. [ 51–53 ] This was explained by the modification of the interfacial electronic states of the FM near the Fermi level by the introduction of those materials with strong spin‐orbit coupling. There is another possibility that the inserted Pt layer could serve as a catalyst to facilitate oxygen ion migration.…”
Section: Resultsmentioning
confidence: 99%
“…For the macrospin simulations, we considered a ferromagnetic disk of thickness t = 0.9 nm, saturation magnetization M s = 1000 kA/m and an out-of-plane effective anisotropy field of µ 0 H K = 80 mT. These parameters are rather usual values for ferromagnetic thin films exhibiting perpendicular magnetic anisotropy (PMA) 29 , 30 and particularly, they are typical for heavy-metal/ferromagnet/oxide systems most common in VCMA studies 14 , 21 , 31 , 32 . This model satisfies magnetic entities with lateral dimensions bellow the domain wall width, which in this case is around 72 nm.…”
Section: Resultsmentioning
confidence: 99%